Eros and creativity in Russian religious renewal : the philosophers and the Freudians - Crone, Anna Lisa (Russian history and culture (Leiden, Netherlands) ;, 2010)
This book is a fascinating exploration of largely uncharted territory in the history of Russian religious thought. Focusing on four brilliant representatives of the "Russian religious renaissance" of the late nineteenth and early twentieth centuries--Vladimir Solovyov, Vasily Rozanov, Nikolai Berdyaev, and Boris Vysheslavtsev--Anna Lisa Crone masterfully details their efforts, which were at first quite independent of the work of Sigmund Freud and later highly critical of it, to establish the importance of the sex drive in human life and to reinterpret Christianity as a religion of th